Narrating post-colonial crisis: the post-colonial state and the individual in the works of Sony Labou Tansi - Mashihi, Thapelo (My University, 2014)
In this study I will examine two texts by the Congolese author Sony Labou Tansi, namely The Seven Solitudes of Lorsa Lopez and Parenthesis of Blood. The aim of the research is to examine how and why the author uses techniques of allegory and magic realism instead of realism in his work. By closely examining the two texts and with the help of comparisons with his other works, I intend to show that the world he is representing is too fabulous to be rendered in a realistic manner. The use of allegory and irony in the text is a strategy that helps the author to challenge the oppression and despair in his society. The issue of gender is also important in both texts, therefore, I will examine how Labou Tansi portrays women in his works. I will do this by comparing his presentation of women to other female characters found in African canonical works by male writers.
Thesis (M.A.)--University of the Witwatersrand, 1999.
Keywords: Magic realism (Literature); Colonial influence--African literature; Postcolonialism; Sony Lab'Ou Tansi. Seven solitudes of Lorsa Lopez; Congolese (Democratic Republic) literature (French)